The Biogeography of Fungal Communities Across Different Chinese Wine-Producing Regions Associated With Environmental Factors and Spontaneous Fermentation Performance - Li, Ruilong; Yang, Siyu; Lin, Mengyuan; Guo, Sijiang; Han, Xiaoyu; Ren, Mengmeng; Du, Le; Song, Yinghui; You, Yilin; Zhan, Jicheng; Huang, Weidong (Frontiers in Microbiology, 2022)
Chinese Marselan grapes are believed to possess the potential to become a characteristic regional variety, whose quality is internationally recognized. The fermentation-related mycobiota from six climatically diverse Marselan-producing regions in China were analyzed via high-throughput sequencing (HTS), while the influence of environmental factors was evaluated as well. The results implied that the phyla Ascomycota and genus Aureobasidium dominated the fungal communities in 166 Marselan must and ferment samples. Significant differences were detected in the fungal microbiota from the regions, as well as the wineries, while these discrepancies decreased as the fermentation progressed. Moreover, the discrepancy in fungal communities between the wineries exceeded the variation involving the regions, and higher diversity was identified in the types of species than in the compositions. Geoclimatic elements (Gc) and physicochemical indexes (Pi) exerted a significant effect on the fungal must consortium, explaining 58.17% of the taxonomic information. Therefore, a correlation was proposed between the spontaneous fermentation performance, as well as the polyphenol (PP) content, and their association with fungal taxonomic composition. In addition to enriching the knowledge regarding the wine microbiome and its influencing factors, this study may provide a new strategy for harnessing autochthonous “microbial terroir”.